Growth of coiled amorphous carbon nanotube array forest and its electromagnetic wave absorbing properties. (1st February 2018) - Hu, Jingtian; Zhao, Tingkai; Peng, Xiarong; Yang, Wenbo; Ji, Xianglin; Li, Tiehu
Abstract: Coiled amorphous carbon nanotube (CACNT) array was prepared by chemical vapor deposition method. The experimental results indicated that the length of as-prepared CACNT array was about 30 μm. The electromagnetic wave absorbing properties were studied through comparison among CACNTs, CACNT-La(NO3 )3, CACNT-(Fe, Co, Ni) and CACNT-reduced graphene oxide (RGO). The experimental results showed the maximum frequency bandwidth of CACNT-(Fe, Co, Ni) was 6.4 GHz below −5 dB and 2.3 GHz below −10 dB separately. Compared to the pure CACNTs, all the frequency bandwidth had been broaden after adding the modified agent. Meanwhile, the additive of rare earth ions La 3+ could effectively increase the maximum absorption peak (−17.94 dB at 8.96 GHz).